Hospitals and urbanism in Rome, 1200-1500 - Keyvanian, Carla (Brill's studies in intellectual history ;, 2015)
"In Hospitals and Urbanism in Rome 1200-1500, Carla Keyvanian offers a new interpretation of the urban development of Rome during three seminal centuries by focusing on the construction of public hospitals. These monumental charitable institutions were urban expressions of sovereignty. Keyvanian traces the political reasons for their emergence and their architectural type in Europe around 1200. In Rome, hospitals ballasted the corporate image of social elites, aided in settling and garrisoning vital sectors and were the hubs around which strategies aimed at territorial control revolved. When the strategies faltered, the institutions were rapidly abandoned. Hospitals in areas of enduring significance instead still function, bearing testimony to the influence of late medieval urban interventions on modern Rome"--Provided by publisher